Hubungan Penggunaan Model Pembelajaran Kooperatif Tipe Group Investigation ( GI ) terhadap Hasil Belajar PKn Siswa Kelas V SD Inpres Minasaupa 1 Kecamatan Rappocini Kota Makassar - Jumiati Nur; Andi Sugiati (Universitas of Muhammadiyah Makassar, 2017)
This research is experimental research by using one class as research sample that is class V with total student 40 peoples. This study aims to determine the relationship between the use of Cooperative Learning Model Type Group Investigation (GI) In Students Class V SD Inpres Minasa Upa 1 with reference to the completeness of learning outcomes, increased student activity of six observed aspects, good teacher activity on the implementation of cooperative learning type Group Investigation (GI). The result of the research shows that: The relationship between the use of cooperative learning model of Group Investigation type and the result of the students' learning in the know from the hypothesis test with the product moment with the result of r = 0.9111 is categorized